Edukacja zdrowotna w szkole w obliczu wyzwań XXI wieku w polskiej oświacie - Dworak, Alina; Rzymelka-Frąckiewicz, Agata (Studia Edukacyjne, 2025)
The life and health of a post-transformation society is determined by the development of civilization, which practically affects all spheres of individual functioning, generating new problems in both the individual and socio-educational dimensions. Dynamic transformations of everyday life extend to all institutions of social life, including the school. The world around us is changing intensely, and the school as we know it is becoming a thing of the past. Observation of the attitudes and behaviors of the younger generation, as well as the rapid and accelerating transformation of the surrounding reality, have become the inspiration and urgent need to take educational and upbringing measures, as part of the process of socialization of the younger generation, in which, in addition to the family, the school and the educator must not be absent. The school as an educational space is a place where health promotion and health education is the primary goal. The school of the 21st century is a modern one, safe and open to the challenges of comprehensive education. Therefore, the challenge for the modern education system is to develop the capacity to make health-promotion choices. This is the task for health education, which should become a major task for the school and the teacher at the center of school health education.